The Current State of Tax Administration in Ukraine: an Analytical Review of Terminology - KOLOMIIETS, Pavlo V. (Journal of Advanced Research in Law and Economics; Vol 8 No 8 (2017): JARLE, Volume VIII, Issue 8(30), Winter 2017DO - 10.14505//jarle.v8.8(30).15, 2018)
Abstract : The article includes the study of contemporary legal problems of regulation of the collection of taxes and fees and submit proposals for their improvement. Analysis of current tax legislation Ukraine, departmental regulations and practices for their implementation, theoretical understanding of scientific works, publications and recent research shows that today urgently needs further reformatting the Tax Code of Ukraine. Recently, discussions around the Tax Code of Ukraine tend to increase. Particularly sharp criticism is about the quality of writing legal text of the Code, its shape and structure. The current topic of contemporary tax debates in Ukraine is the imperfection of the current norms of the Tax Code. The generally acknowledged problem in the field of tax legislation is recognized by the language and technical quality of tax law-making. Consequently, the study of legal problems in the regulation of relations in the field of collecting taxes and fees shows that one of the principles on which the tax legislation of Ukraine should be based on the principle of uniqueness and stability of the meanings of concepts. In accordance with them, the legal rules of the tax legislation should be formulated clearly. Legal terms should be used in the texts of tax legislation in a logical and consistent manner. That is, the formation of tax terms, their consolidation in modern tax legislation should take place on their own tax base. Imperative provisions of the Tax Code of Ukraine, which are based on positive obligations must provide clarity, intelligibility of tax regulations. Another problem, in our opinion, is the question of efficient use in existing Ukrainian tax legislation concepts of ‘special tax regime’, ‘generic tax regime’, ‘tax regime’, ‘special regime’.